Pengaruh Celebrity Endorser Hamidah Rachmayanti Terhadap Keputusan Pembelian Produk Online Shop MAYOUTFIT Di Kota Bandung - Ratika Zahra; Nofha Rina (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2018)
Utilization of internet among modern society today is the use of social media. Of the many social media that are present to be consumed by modern society and one of them is Instagram useful benefits for the delivery of new information including one that is also used dalah things do business. The emergence of the phenomenon of online shopping in social media Instagram for the vigorous business conduct marketing using supporting figures or celebrities endorser as a supporter to market their products. Seeing this phenomenon, it is necessary to do a research that.Â Hamidah Rachmayanti is a celebrity endorser used by Online Shop Mayoutfit has several purposes in this research is to determine the effect of Visibility, Credibility, Attractiveness and Celebrity Endorser Effectiveness to the Decision Purchase Online Shop Mayoutfit products. This research uses quantitative method with questionnaire distribution and using multiple linear regression.Â This study concludes that the influence of Celebrity Endorser on @hamidahrachmayanti account of 52.1% can be explained by variables consisting of Visibility, Credibility, Attractiveness, and Power.Â